The Mediating Role of Work Motivation on the Influence of Performance Rewards on Soldier Performance at Work Unit XYZ - Achmad Surya Manggara; Wiyarni Wiyarni (Universitas KH. Abdul Chalim Mojokerto, 2025)
One of the major institutions or organizations in Indonesia is the Indonesian National Army (TNI). The TNI itself consists of three forces, namely the TNI of the Armed Forces, the Navy and the Air. In the conditions of carrying out his duties or responsibilities for a TNI, he must have a good performance is the result of optimum work in accordance with organizational standards and support the achievement of the goals of the organization. The purpose of the research is to analyse the impact of performance benefits on performance through the mediation of work motivation. The research method used is a type of survey method with a quantitative approach. With the SEM-PLS analysis tool which includes a sample of 51 respondents in the XYZ TNI AU Labour Unit. The research results show that performance benefits do not have a significant effect on employee performance, but performance benefits have a positive and significant impact on employment motivation. The study also found that work motivation has a positive impact as well as significant on performance. Furthermore, the motivation of work as a mediator shows the positive and significant impact of performance benefits on employees performance. The implications of the research show that the performance benefits are positive and not significantly influenced by soldiers performance. However, with the job motivation as the mediator is able to make performance benefits influence career performance, it is recommended that the TNI XYZ AU Labor Unit continue and improve the development of employee benefits system.